Comparison of Franseen and fork-tip needles for EUS-guided fine-needle biopsy of solid mass lesions: A systematic review and meta-analysis - Mohan, Babu P. (Endosc Ultrasound, 2019)
Franseen-tip and Fork-tip needles have been widely used in EUS guided fine-needle biopsy (FNB) of solid organs. There is conflicting data on the performance of these needles and unanswered questions on the ideal number of needle-passes and the requirement of an onsite cytopathologist (ROSE). We conducted a comprehensive search of multiple electronic databases and conference proceedings including PubMed, EMBASE, and Web of Science databases (from inception through July 2018) to identify studies that reported on the use of Forktip and Franseen-tip needles in EUS-FNB of solid organs. The primary outcome was to estimate and compare the pooled rates of diagnostic-yield. A subgroup analysis compared the outcomes based on the number of needle-passes and the availability of ROSE. A total of 23 study-arms were available for analysis. The pooled rate of diagnostic yield with Fork-tip needle was 92.8% (95% CI 85.3 - 96.6, I(2) = 73.1) and the pooled rate of diagnostic yield with Franseen-tip needle was 92.7% (95% CI 86.4 - 96.2, I(2) = 88.4).